A biodegradable foaming material and preparation method thereof
By using raw materials such as polyadipic acid/butylene terephthalate, polylactic acid and dextropolylactic acid-polycaprolactone grafts in biodegradable foams, combined with modification reactions and physical foaming processes , solve the problems of low cell density and unevenness, and achieve biodegradable foaming materials with high foaming ratio and uniform cell size, improving the mechanical properties of the material and market application value.
Patent Information
- Application Number
- CN202111434042.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-11-29
AI Technical Summary
During the foaming process, existing biodegradable foam plastics have problems such as low cell density, uneven cell size and low foaming ratio. Especially, the melt strength of PBAT/PLA blend materials is reduced due to thermodynamic incompatibility. Uneven cell cells.
The raw materials including polyadipic acid/butylene terephthalate, polylactic acid, dextropolylactic acid-polycaprolactone grafts, plasticizers, crosslinking agents, anti-hydrolytic agents and heat stabilizers are used. Through the modification reaction and physical foaming process, a biodegradable foaming material with high foaming magnification and uniform foaming cells is formed. Dextropolylactic acid-polycaprolactone grafts form SC crystals during processing, promote nucleation, and control cell nucleation through PCL segments, crosslinking agents and anti-hydrolyzers to improve material interfaces and melt strength.
It has achieved a biodegradable foaming material with fine cell, uniformity, high foaming ratio and good mechanical properties. It is suitable for high-end buffer packaging and has a high market value.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bio-based polymer materials, and in particular to a biodegradable foaming material and a preparation method thereof. Background Art
[0002] For more than half a century, petroleum-based non-degradable plastics have been widely used in daily life and in industrial and agricultural fields, but have also caused large-scale "white pollution", greenhouse gas emissions and consumption of petrochemical energy. In particular, disposable products such as plastic packaging shopping bags, plastic lunch boxes, foam products, etc. are widely used and then discarded in natural environments such as oceans, farmlands and lakes, seriously endangering human physical and mental health and becoming a global public hazard.
[0003] In order to solve the problem of "white pollution", there are currently two main research directions, one is the recycling and reuse of waste plastics, and the other is the research on biodegradable plastics.
[0004] Biodegradable plastics refer to products whose performance can meet the use requirements during the use and storage period, and can be completely degraded into carbon dioxide and water under natural environment (water, oxygen, heat and microorganisms, etc.) after use and disposal. Most biodegradable plastics begin to become thinner, lose weight, and lose strength after being exposed to the natural environment for 3-6 months, and gradually break into pieces, and then gradually begin to degrade. In fact, biodegradable materials are an important way to solve "white pollution", achieve energy conservation and carbon reduction, and achieve sustainable development. Therefore, biodegradable foam materials have attracted widespread attention due to their biodegradability. The rapid development of biodegradable materials based on renewable resources has become an inevitable trend.
[0005] At present, the research and application of biodegradable foam plastics by scholars at home and abroad are mainly focused on polymers such as polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS) and starch. Among them, PBAT, PLA or PBAT / PLA blended alloy materials are mainly used for foaming. The performance of their products can reach or approach the performance standards of PE, EVA and PET foam products, and can completely replace petroleum-based non-degradable plastic products.
[0006] However, PBAT, PLA or PBAT / PLA blended foaming materials often have disadvantages such as low cell density, large cells and uneven distribution. Especially in the foaming process of PBAT / PLA blended materials, due to the thermodynamic incompatibility between PBAT and PLA, there is less entanglement between the segments of different materials, resulting in a decrease in melt strength. Inorganic nucleating agents are often added to control the nucleation of the cells, but inorganic nucleating agents are often particles with uneven particle sizes, so they are also prone to uneven cell sizes and low foaming ratios.
[0007] The contents of the background technology section are merely the technologies known to the inventors and do not necessarily represent the prior art in the field. Summary of the invention
[0008] In order to solve the above-mentioned prior art problems, the present application aims to provide a biodegradable foaming material and a preparation method thereof. The foamed product prepared by the method has fine and uniform pores, a high foaming ratio, and good mechanical properties.
[0009] According to one aspect of the present application, a biodegradable foaming material is prepared from raw materials including the following components:
[0010] Polybutylene adipate / terephthalate 64.0-88.15%;
[0011] Polylactic acid 10-30%;
[0012] Dextrorotatory polylactic acid-polycaprolactone grafted compound 0.5-3%;
[0013] Plasticizer 0.5-1%;
[0014] Cross-linking agent 0.1-0.5%;
[0015] Anti-hydrolysis agent 0.25%-0.5%;
[0016] Heat stabilizer 0.5%-1%.
[0017] According to some embodiments of the present application, the polybutylene adipate / terephthalate has a melt index of 2.5-10 g / 10 min and a melting point of 116-122° C.
[0018] According to some embodiments of the present application, the melt index is 2.5-5 g / 10 min.
[0019] According to some embodiments of the present application, the polylactic acid is poly-L-lactic acid.
[0020] According to some embodiments of the present application, the optical purity of the poly L-lactic acid is ≥96%, and the melting point is 140-180°C.
[0021] According to some embodiments of the present application, the optical purity of the poly L-lactic acid is 98% and the melting point is 160-170°C.
[0022] According to some embodiments of the present application, the plasticizer is selected from one or more of aliphatic dibasic acid esters, phthalic acid esters, polybenzoic acid esters, benzoic acid esters, polyol esters, chlorinated hydrocarbons, epoxies, citrates and polyester plasticizers.
[0023] According to some embodiments of the present application, the cross-linking agent is selected from one or more of benzoyl peroxide, di-tert-butyl peroxide and dicumyl peroxide.
[0024] According to some embodiments of the present application, the anti-hydrolysis agent is selected from one or more of epoxy compounds and mono / polycarbodiimides.
[0025] According to some embodiments of the present application, the heat stabilizer is selected from one or more of calcium stearate, zinc stearate, and barium stearate.
[0026] According to some embodiments of the present application, the dextrorotatory polylactic acid segment of the dextrorotatory polylactic acid-polycaprolactone graft compound forms SC crystals in situ with the polylactic acid.
[0027] According to another aspect of the present application, a method for preparing a biodegradable foaming material is provided, comprising:
[0028] The raw materials including poly(butylene adipate / terephthalate), poly(lactic acid), dextrorotatory poly(lactic acid)-poly(caprolactone) graft, plasticizer, crosslinking agent, anti-hydrolysis agent and thermal stabilizer are uniformly mixed and then subjected to modification reaction to obtain a modified material;
[0029] The modified material is fed into a physical foaming sheet extruder for continuous extrusion to obtain the biodegradable foaming material.
[0030] According to some embodiments of the present application, the modification reaction temperature is 180-190°C.
[0031] According to some embodiments of the present application, the temperature of the physical foaming sheet extruder is 120-180°C, the die head temperature is controlled at 105-110°C, the CO2 injection pressure is 12-20MPa, and the barrel pressure is 12-18MPa.
[0032] According to some embodiments of the present application, the preparation method of the dextrorotatory polylactic acid-polycaprolactone graft comprises:
[0033] Add the dried dextrorotatory polylactic acid and polycaprolactone into a high-speed mixer, add 0.5-1% of the total weight of plasticizer and 2-3% of the chain extender while stirring, mix the materials thoroughly and evenly for use;
[0034] The obtained mixture is added into an internal mixer, and after the reaction torque balance no longer increases, extrusion granulation is performed to obtain the product.
[0035] According to some embodiments of the present application, the mass ratio of dextrorotatory polylactic acid to polycaprolactone is 1:2-2:1.
[0036] According to some embodiments of the present application, the rotation speed of the high-speed mixer is 500-1000 r / min, and the mixing time is 30-60 s.
[0037] According to some embodiments of the present application, the rotation speed of the internal mixer is 30-40 r / min, the rotor temperature is controlled at 180-190° C., and the internal mixing time is 4-6 min.
[0038] According to some embodiments of the present application, the chain extender includes: cyanate esters, epoxies, anhydrides, phosphites or peroxides.
[0039] According to some embodiments of the present application, the chain extender is an epoxy chain extender.
[0040] According to an embodiment of the present application, the present application provides a biodegradable foaming material, which is made from raw materials including the following components: polybutylene adipate / terephthalate, polylactic acid, dextrorotatory polylactic acid-polycaprolactone graft, plasticizer, cross-linking agent, anti-hydrolysis agent, and thermal stabilizer.
[0041] The preparation method of the present application is based on conventional bio-based and degradable materials and traditional processes. The initial production equipment investment and later production costs are similar to those of traditional petroleum-based non-degradable materials. The product of the present application has good mechanical properties, a foaming ratio ≥15 times, and a pore size ≤100 microns.
[0042] The right-handed polylactic acid-polycaprolactone graft of the present application can simultaneously generate two nucleation modes in the system. First, the PDLA segment and PLA form relatively uniform SC crystals (nanoscale nucleus size, α type) in situ during the processing process. The SC crystals have the function of promoting the nucleation of the system. Second, the PCL segment plays the role of an elastomer in the system. The different thermal expansion coefficients of PCL and the alloy material are used to control the generation of pores between the two phases and better control the nucleation of the pores.
[0043] In addition, the phase interface of the PBAT / PLA blend prepared by the cross-linking agent and the anti-hydrolysis agent is also improved, the chain entanglement is increased, and the melt strength is also increased, so the obtained foam product has a high ratio, a high pore density, and smaller pores and a more uniform distribution.
[0044] According to an embodiment of the present application, the present application provides a method for preparing a biodegradable foaming material, comprising: stirring the raw materials evenly, blending and modifying them through a twin-screw extruder, extruding and granulating them, and drying them to obtain a modified material; putting the modified material into a physical foaming sheet extruder for continuous extrusion to obtain a foaming material.
[0045] This method uses SC crystals generated in situ by PDLA and PLA to promote the nucleation of the system. The SC crystals have a small particle size and are uniform in size. In addition, the PCL at the end of the graft, due to the effect of the epoxy group of the chain extender, limits the crystallization of PCL to a certain extent. In the PBAT / PLA system, it plays the role of an elastomer. The different thermal expansion coefficients of PCL and the alloy material are used to control the generation of pores between the two phases, and the nucleation of the foam cells is better controlled. The prepared foam products have high cell density, small cells and more uniform distribution. The prepared foam products have high application prospects and market value in high-end product cushioning packaging. DETAILED DESCRIPTION
[0046] As mentioned above, most of the current bio-based foaming materials have the disadvantages of low cell density, large cells and uneven distribution of cells. In view of the above problems, the present application provides a biodegradable foaming material and a preparation method thereof.
[0047] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application. Therefore, the description is considered to be exemplary rather than restrictive in nature.
[0048] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.
[0049] In this application, the terms "first", "second", and other ordinal numbers are used only for descriptive purposes and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, "plurality" means two or more, unless otherwise clearly and specifically defined.
[0050] It should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be directly connected, or indirectly connected through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this disclosure can be understood according to specific circumstances.
[0051] The following is a more detailed description of the specific implementation of the present application in conjunction with the examples, so that the scheme of the present application and its advantages in various aspects can be better understood. However, the specific implementation and examples described below are only for the purpose of illustration, and are not intended to limit the present application.
[0052] Except in relation to charge, "%" in this application means "mass percentage".
[0053] A biodegradable microporous high-rate extrusion foaming material is prepared from raw materials comprising the following components in percentage by mass:
[0054] Polybutylene adipate / terephthalate 64.0-88.15%;
[0055] Polylactic acid 10-30%;
[0056] Dextrorotatory polylactic acid-polycaprolactone grafted compound 0.5-3%;
[0057] Plasticizer 0.5-1%;
[0058] Cross-linking agent 0.1-0.5%;
[0059] Anti-hydrolysis agent 0.25%-0.5%;
[0060] Heat stabilizer 0.5%-1%.
[0061] Specifically, the PBAT is polybutylene adipate / terephthalate, with a melt index of 2.5-10 g / 10 min (190° C., 2.16 kg) and a melting point of 116-122° C.; optionally, the melt index is 2.5-5 g / 10 min (190° C., 2.16 kg).
[0062] Specifically, the PLA is poly L-lactic acid with an optical purity of ≥96% and a melting point of 140-180°C; optionally, it is poly L-lactic acid with an optical purity of 98% and a melting point of 160-170°C.
[0063] The present application selects PBAT and PLA with the above parameters as raw materials, and the prepared product has stable performance and controllable process. Those skilled in the art can select raw materials with other parameter ranges according to the process.
[0064] Since PBAT (polybutylene adipate / terephthalate) is a relatively soft material, it is often blended with PLA (polylactic acid) to increase mechanical strength. However, biodegradable materials are polyester structures, which are easily hydrolyzed in high temperature environments, thereby increasing fluidity and reducing melt strength. This application suppresses the hydrolysis of PBAT and PLA by adding a certain proportion of anti-hydrolysis agents, and appropriately improves the melt strength of the blended material through cross-linking agents.
[0065] During the foaming process of PBAT / PLA blends, the melt strength decreases due to the thermodynamic incompatibility between PBAT and PLA and less entanglement between chain segments of different materials. Inorganic nucleating agents are often particles with uneven particle sizes, which can easily lead to uneven pore size and a low foaming ratio.
[0066] The PDLA segments and PLA in the dextrorotatory polylactic acid-polycaprolactone graft prepared in the present application in situ form SC crystals with relatively uniform size (nanoscale crystal core size, α-type) during the processing, which can promote the nucleation of the system.
[0067] At the same time, PCL plays the role of an elastomer in the system. The different thermal expansion coefficients of PCL and the alloy material are utilized to control the generation of pores between the two phases and better control the nucleation of the pores.
[0068] In addition, the phase interface of the PBAT / PLA blend prepared by the cross-linking agent and the anti-hydrolysis agent is also improved, the chain entanglement is increased, and the melt strength is also increased, so the obtained foam product has a high ratio, a high pore density, and smaller pores and a more uniform distribution.
[0069] Therefore, the two nucleation methods of right-handed polylactic acid-polycaprolactone grafts complement each other and control the foam cells more evenly, making the foam pores more delicate and uniform, with a higher texture, and will have greater application prospects and market value in the high-end cushioning packaging market.
[0070] The grafted product of dextrorotatory polylactic acid (PDLA) and polycaprolactone (PCL) of the present application is prepared by the following steps:
[0071] (1) Dry PDLA and PCL in a vacuum oven at 60-70°C and 40-50°C for 24 hours respectively, then add them into a high-speed mixer at a mass ratio of 1:1, stir at a low speed, add 0.5-1% of the total mass of PDLA and PCL plasticizer and 2-3% of the chain extender while stirring, rotate at 500-1000 r / min, and mix for 30-60 seconds until the materials are fully mixed and evenly mixed for later use;
[0072] (2) Add the mixture obtained in step (1) into an internal mixer according to the amount, set the rotor speed to 30-40 r / min, control the rotor temperature to 180-190° C., and mix for 4-6 min. After the reaction torque balance no longer increases, extrude and granulate the mixture, and vacuum pack it for later use.
[0073] Specifically, the chain extender includes cyanate esters, epoxies, anhydrides, phosphites or peroxides.
[0074] Optionally, the chain extender is an epoxy chain extender.
[0075] The plasticizers include aliphatic dibasic acid esters, phthalic acid esters (including phthalic acid esters and terephthalic acid esters), polyphenylene esters, benzoic acid esters, polyol esters, chlorinated hydrocarbons, epoxies, citrate esters, polyesters, and the like.
[0076] Optionally, the plasticizer is epoxidized soybean oil (ESO), acetyl tributyl citrate or polyethylene glycol.
[0077] The present application also provides a method for preparing the above-mentioned biodegradable microporous high-ratio extrusion foaming material, comprising the following steps:
[0078] (1) The raw materials poly(butylene adipate / terephthalate), poly(lactic acid), dextrorotatory poly(lactic acid-polycaprolactone) graft, plasticizer, crosslinking agent, anti-hydrolysis agent and thermal stabilizer are uniformly stirred in a high-speed mixer, and then blended, modified and extruded into granules by a twin-screw extruder at 180-190°C, and dried for later use;
[0079] (2) The modified material obtained in step (1) is put into a physical foaming sheet extruder (CO2 is used as a foaming agent), the temperature is controlled at 120-180°C, the die head temperature is controlled at 105-110°C, the CO2 injection pressure is 12-20MPa, and the barrel pressure is 12-18MPa, and then continuously extruded and cut to obtain foamed products of corresponding sizes.
[0080] Specifically, the cross-linking agent is benzoyl peroxide, di-tert-butyl peroxide or dicumyl peroxide;
[0081] Optionally, the cross-linking agent is dicumyl peroxide (DCP).
[0082] The anti-hydrolysis agent is an epoxy compound, a mono / polycarbodiimide, etc.
[0083] Optionally, the anti-hydrolysis agent is a polycarbodiimide anti-hydrolysis agent.
[0084] The heat stabilizer is calcium stearate, zinc stearate or barium stearate;
[0085] Optionally, the heat stabilizer is calcium stearate.
[0086] The plasticizer is aliphatic dibasic acid esters, phthalic acid esters (including phthalic acid esters and terephthalic acid esters), polyphenylene esters, benzoic acid esters, polyol esters, chlorinated hydrocarbons, epoxies, citrate esters, polyesters, and the like.
[0087] Optionally, the plasticizer is epoxidized soybean oil (ESO), acetyl tributyl citrate or polyethylene glycol.
[0088] The present application is described below with reference to specific embodiments. The process condition values taken in the following embodiments are all exemplary. For process parameters not specifically noted, conventional techniques may be used. Unless otherwise specified, the detection methods used in the following embodiments are conventional detection methods in the industry. Unless otherwise specified, the reagents and instruments used in the technical solutions provided in this application can be purchased from conventional channels or the market.
[0089] Example 1
[0090] The biodegradable foam material of the present application is prepared from the following raw materials in percentage by mass:
[0091] PBAT: 80.75%; PLA: 15%; PDLA-PCL: 2%; ESO: 0.5%; DCP: 0.25%; Polycarbodiimide: 0.5%; Calcium stearate: 1%.
[0092] Preparation method of the above foaming material:
[0093] (1) Physically mix the above raw materials evenly with a high-speed mixer;
[0094] (2) The mixture of step (1) is blended and modified by a twin-screw extruder at 185-190° C., and extruded, pelletized, collected, and dried.
[0095] (3) The material is put into a physical foaming sheet extruder (CO2 as a foaming agent), the temperature is controlled at 120-180°C, the die temperature is controlled at 105-110°C, the CO2 injection pressure is 12-20MPa, and the barrel pressure is 12-18MPa. Then it is continuously extruded and cut to obtain foamed products of corresponding sizes. The product has fine pores, no obvious merging phenomenon, and good mechanical properties.
[0096] Example 2
[0097] The biodegradable foam material of the present application is prepared from the following raw materials in percentage by mass:
[0098] PBAT: 64%; PLA: 30%; PDLA-PCL: 3%; ESO: 1%; DCP: 0.5%; Polycarbodiimide: 0.5%; Calcium stearate: 1%.
[0099] Preparation method of the above foaming material:
[0100] (1) Physically mix the above raw materials evenly in a high-speed mixer;
[0101] (2) At 180-190°C, the mixture is blended and modified by a twin-screw extruder, and then extruded, pelletized, collected, and dried.
[0102] (3) The material is put into a physical foaming sheet extruder (CO2 is used as a foaming agent), the temperature is controlled at 120-180°C, the die temperature is controlled at 105-110°C, the CO2 injection pressure is 12-20MPa, and the barrel pressure is 12-18MPa. Then, continuous extrusion is performed and cutting is performed to obtain foamed products of corresponding sizes.
[0103] The product has fine pores, no obvious merging phenomenon, and good mechanical properties.
[0104] Example 3
[0105] The biodegradable foam material of the present application is prepared from the following raw materials in percentage by mass:
[0106] PBAT: 88.15%; PLA: 10%; PDLA-PCL: 0.5%; ESO: 0.5%; DCP: 0.1%; Polycarbodiimide: 0.25%; Calcium stearate: 0.5%.
[0107] Preparation method of the above foaming material:
[0108] (1) Physically mix the above raw materials evenly in a high-speed mixer;
[0109] (2) At 185-190°C, the mixture is blended and modified by a twin-screw extruder, and then extruded, pelletized, collected, and dried.
[0110] (3) The material is put into a physical foaming sheet extruder (CO2 is used as a foaming agent), the temperature is controlled at 120-180°C, the die temperature is controlled at 105-110°C, the CO2 injection pressure is 12-20MPa, and the barrel pressure is 12-18MPa. Then, continuous extrusion is performed and cutting is performed to obtain foamed products of corresponding sizes.
[0111] The product has fine pores, no obvious merging phenomenon, and good mechanical properties.
[0112] Comparative Example 1 <Adding Inorganic Nucleating Agent—Talc>
[0113] A biodegradable foaming material, composed of the following raw materials in percentage by mass:
[0114] PBAT: 80.75%; PLA: 15%; Talc: 2%; ESO: 0.5%; DCP: 0.25%; Polycarbodiimide: 0.5%; Calcium stearate: 1%.
[0115] The preparation method of the above foaming material is the same as that of Example 1.
[0116] The pores of the product are fine as a whole, but some of them are merged.
[0117] Comparative Example 2 <Addition of Inorganic Nucleating Agent—Silicon Dioxide>
[0118] A biodegradable foaming material, composed of the following raw materials in percentage by mass:
[0119] PBAT: 64%; PLA: 30%; Silicon dioxide: 3%; ESO: 1%; DCP: 0.5%; Polycarbodiimide: 0.5%; Calcium stearate: 1%.
[0120] The preparation method of the above foaming material is the same as that of Example 2.
[0121] The product has normal pores, but there is a phenomenon of pore merging.
[0122] Comparative Example 3 <Addition of Ungrafted PDLA>
[0123] A biodegradable foaming material, composed of the following raw materials in percentage by mass:
[0124] PBAT: 88.15%; PLA: 10%; PDLA: 0.5%; ESO: 0.5%; DCP: 0.1%; Polycarbodiimide: 0.25%; Calcium stearate: 0.5%.
[0125] The preparation method of the above foaming material is the same as that of Example 3.
[0126] Although the product has fine pores, there is a phenomenon of pore merging.
[0127] Comparative Example 4 <Addition of Ungrafted PCL>
[0128] A biodegradable foaming material, composed of the following raw materials in percentage by mass:
[0129] PBAT: 88.15%; PLA: 10%; PCL: 0.5%; ESO: 0.5%; DCP: 0.1%; Polycarbodiimide: 0.25%; Calcium stearate: 0.5%.
[0130] The preparation method of the above foaming material is the same as that of Example 3.
[0131] The pores in the product are of different sizes and there is a phenomenon of pore merging.
[0132] Comparative Example 5 <Addition of Ungrafted PDLA and PCL>
[0133] A biodegradable foaming material, composed of the following raw materials in percentage by mass:
[0134] PBAT: 88.15%; PLA: 10%; PDLA: 0.25%; PCL: 0.25%; ESO: 0.5%; DCP: 0.1%; Polycarbodiimide: 0.25%; Calcium stearate: 0.5%.
[0135] The preparation method of the above foaming material is the same as that of Example 3.
[0136] Although the product has fine pores, there is a phenomenon of pore merging.
[0137] Test example
[0138] The samples obtained from Examples 1-3 and Comparative Examples 1-5 were selected for performance testing, and the testing method was as follows:
[0139] (1) Apparent density test: in accordance with GB / T 6343-2009 “Determination of apparent density of cellular plastics and rubber”;
[0140] (2) Foaming ratio: ; Wherein, ρ0 is the density of the unfoamed modified particles, and ρf is the density of the modified foam product;
[0141] (3) Cell density: The foamed sample was cooled and quenched by liquid nitrogen, and the surface of the cross section was sprayed with gold. The cell structure of the PBAT / PLA alloy foamed material was characterized by SEM. The structure of the foam was observed at a magnification of 200 times and the cell density was calculated. The cell density was analyzed by computer software Image Tool and calculated by the following formula:
[0142]
[0143] Where: Nc - cell density, pieces / cm3; nb - number of cells in the statistical area, pieces;
[0144] ρ0 - the density of unfoamed modified particles, ρf - the density of modified foam products;
[0145] The test results are shown in Table 1:
[0146] Table 1 Performance test results
[0147] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Apparent density (g / cm 3 ).]]> 0.062 0.081 0.072 0.107 0.120 0.100 0.091 0.088 Foaming ratio (times) 21.7 15.3 18.5 12.6 10.4 13.1 14.6 15.1 Average pore size (μm) 18.61 37.56 23.84 128.16 98.47 79.62 53.89 42.73 <![CDATA[Cell density (pcs / cm 3 )]]> <![CDATA[2.83×10 9 ]]> <![CDATA[7.18×10 8 ]]> <![CDATA[9.45×10 8 ]]> <![CDATA[3.77×10 8 ]]> <![CDATA[5.62×10 8 ]]> <![CDATA[1.26×10 8 ]]> <![CDATA[3.74×10 8 ]]> <![CDATA[5.83×10 8 ]]>
[0148] From the above composition and results, it can be seen that the main materials of the present application are completely degradable materials and have good mechanical properties. The foaming ratio of the foamed product in the embodiment is ≥15 times, the pore size is ≤100 microns, and the product can be fully commercialized.
[0149] Finally, it should be noted that the above is only a preferred embodiment of the present application and is not intended to limit the present application. Although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A biodegradable foaming material, It is characterized in that It is prepared from the following raw materials with the following mass percentage components: Polybutylene adipate / terephthalate 80.75-88.15%; Polylactic acid 10-15%; Dextrorotatory polylactic acid-polycaprolactone grafted compound 0.5-3%; Plasticizer 0.5-1%; Cross-linking agent 0.1-0.5%; Anti-hydrolysis agent 0.25-0.5%; Heat stabilizer 0.5-1%; Wherein, the polylactic acid is poly-L-lactic acid; the foaming agent is CO 2 ; The optical purity of the poly L-lactic acid is ≥96%, and the melting point is 140-180°C; the melting index of the polybutylene adipate / terephthalate is 2.5-10g / 10min, and the melting point is 116-122°C.
2. The foaming material according to claim 1, It is characterized in that The optical purity of the poly L-lactic acid is 98%, and the melting point is 160-170°C.
3. The foaming material according to claim 1, It is characterized in that The plasticizer is selected from one or more of aliphatic dibasic acid esters, phthalic acid esters, benzoic acid esters, chlorinated hydrocarbons, epoxies and citrates.
4. The foaming material according to claim 1, It is characterized in that The cross-linking agent is selected from one or more of benzoyl peroxide and di-tert-butyl peroxide.
5. The foaming material according to claim 1, It is characterized in that The anti-hydrolysis agent is selected from one or more of epoxy compounds, monocarbodiimides and polycarbodiimides.
6. The foaming material according to claim 1, It is characterized in that The heat stabilizer is selected from one or more of calcium stearate, zinc stearate and barium stearate.
7. A method for preparing the biodegradable foaming material according to any one of claims 1 to 6, It is characterized in that include: The raw materials including poly(butylene adipate / terephthalate), poly(lactic acid), dextrorotatory poly(lactic acid)-poly(caprolactone) graft, plasticizer, crosslinking agent, anti-hydrolysis agent and thermal stabilizer are uniformly mixed and then subjected to modification reaction to obtain a modified material; The modified material is fed into a physical foaming sheet extruder for continuous extrusion to obtain the biodegradable foaming material.
8. The preparation method according to claim 7, It is characterized in that The modification reaction temperature is 180-190°C; The physical foaming sheet extruder temperature is 120-180°C, the die head temperature is 105-110°C, and the CO 2 The injection pressure is 12-20MPa and the barrel pressure is 12-18MPa.
9. The preparation method according to claim 8, It is characterized in that The preparation method of the dextrorotatory polylactic acid-polycaprolactone grafted product comprises: Add the dried dextrorotatory polylactic acid and polycaprolactone into a high-speed mixer, add 0.5-1% of the total weight of plasticizer and 2-3% of the chain extender while stirring, and mix the materials thoroughly and evenly for use; The obtained mixture is added into an internal mixer, and after the reaction torque balance no longer increases, extrusion granulation is performed to obtain the product.
10. The preparation method according to claim 9, It is characterized in that The mass ratio of the dextrorotatory polylactic acid to polycaprolactone is 1:2-2:
1.
11. The preparation method according to claim 9, It is characterized in that The speed of the high-speed mixer is 500-1000 r / min, and the mixing time is 30-60 s.
12. The preparation method according to claim 9, It is characterized in that The rotating speed of the internal mixer is 30-40 r / min, the rotor temperature is controlled at 180-190° C., and the internal mixing time is 4-6 min.
13. The preparation method according to claim 9, It is characterized in that The chain extender includes: epoxides, anhydrides, phosphites or peroxides.
